The concept of wasatiyyah under Islamic law perspective: a manifestation of just and balanced rule - Hj Ibrahim, Badruddin; Mohd, Azizah; Hussin, Nasimah; Zawawi, Majdah; Mohd Kamal, Mohd Hisham; Arifin, Mahamad; Mohd Napiah, Mohammad Deen; Omar, Muhammad Naim; Jusoh, Hamid; Ab Aziz, Shamrahayu (Harun M. Hashim Law Centre, 2023)
This article examines the concept of wasatiyyah that is employed and incorporated in various Islamic legal principles and rules of fiqh. Even though such wasatiyyah concept is embodied in various subjects of Islamic law (fiqh), nevertheless, this chapter will only demonstrate several subjects that incorporate wasatiyyah as one of its criteria serving as examples. Therefore, not limited to these preferred subjects, this chapter will discuss the concept of wasatiyyah that is characterized and reflected in several concepts under Islamic law on worship (ibadah), Islamic Family law, Islamic Criminal law, Islamic law on International Relations, Islamic law of Finance as well as Islamic procedural laws Civil and Criminal. The research is basically a qualitative research and doctrinal study. The findings of this research reflect the incorporation of wasatiyyah concept in various fields of Islamic law as a manifestation of a just and balanced rule.